2000
DOI: 10.25249/0375-7536.2000301126129
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Superproduction of the Continental Crust During Paleoproterozoic in South American Platform. Implications Regarding the Interpretative Value of the Sm-Nd Model Ages

Abstract: The production of juvenile continental crust was larger in the Proterozoic than Archean. During Proterozoic the production was about 64%, while during Archean was around 34% of the total volume. The great accretion from mantle to crust happened between 2,2 to 1,9Ga corresponding 35% of the total volume of the actual continental crust. During Archean an intense recycling between mantle and continental crust took place, while in Paleoproterozoic the rate of mantle accretion to continental crust was larger than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
2
0
3
Order By: Relevance
“…Na tabela 2 encontram-se as idades T DM calculadas segundo parâmetros para duplo estágio sugeridos por Sato & Siga Jr. (2000) e DePaolo et al (1991). Os valores obtidos indicam fonte de idade paleoproterozoica para o granito, situando-se assim em período de expressiva geração de crosta continental (Cordani & Sato 1999 Nd dos dois grupos de rochas, sugerindo participação de segmentos crustais distintos para a sua formação.…”
Section: Tabela 1 -Análises Químicas De Elementos Maiores Menores (%unclassified
“…Na tabela 2 encontram-se as idades T DM calculadas segundo parâmetros para duplo estágio sugeridos por Sato & Siga Jr. (2000) e DePaolo et al (1991). Os valores obtidos indicam fonte de idade paleoproterozoica para o granito, situando-se assim em período de expressiva geração de crosta continental (Cordani & Sato 1999 Nd dos dois grupos de rochas, sugerindo participação de segmentos crustais distintos para a sua formação.…”
Section: Tabela 1 -Análises Químicas De Elementos Maiores Menores (%unclassified
“…On the one hand, this is an advantage, because now we know some parts of the history with much greater accuracy than in the past. Moreover, not all geochronological data refl ect the same type of event: samarium-neodymium (Sm-Nd) model ages record the fi rst differentiation of granitic rocks from the earth's mantle (Cordani & Sato 1999;Sato & Siga 2000), an age that may considerably predate the date of actual emplacement of a granite pluton in an orogen. In the early years, for instance, 1.2 Ga (= giga annum, 10 9 years) potassium-argon (K-Ar) mica ages in the Colombian Amazonia were considered to refl ect the age of the rocks themselves (Pinson et al 1962), while later rubidiumstrontium (Rb-Sr) studies (Priem et al 1982) demonstrated this age to represent a later metamorphic overprint over an older rock.…”
Section: Main Subdivisions Of the Amazonian Cratonmentioning
confidence: 99%
“…But even though 'reworked' and 'juvenile' magmas can be distinguished on the basis of Nd and Sr systematics (Cordani & Sato, 1999;Sato & Siga 2000), these methods fall short when it comes to the reconstruction of plausible geodynamic scenarios. But even though 'reworked' and 'juvenile' magmas can be distinguished on the basis of Nd and Sr systematics (Cordani & Sato, 1999;Sato & Siga 2000), these methods fall short when it comes to the reconstruction of plausible geodynamic scenarios.…”
Section: Central-western Granitoid Provinces (Tapajos-ventuari/parimamentioning
confidence: 99%
“…(Figura 01). Esses eventos de colisão ocorreram no início do Proterozoico, como parte da Orogênese Transamazônica (Atlântida) na América do Sul e da Orogenia Eburnianna na África Ocidental, que correspondem à orogênese do Atlântida: com efeito, no seio do embasamento sul-americano, cerca de 54% dos terrenos datam dessa aglutinação, enquanto 35% dos terrenos são arqueanos (portanto, de idade pré-aglutinação do Atlântida) (SATO & SIGA JR;2000, TEXEIRA. et.…”
Section: Materiais E Métodosunclassified